Realistic Mathematics Education (RME) Model on Conversion and Addition of Units of Weight with the Topic of Sidoarjo Milkfish Auction in Elementary School - Amanda, Kartika Budi; Rahmawati, Ika; Wiryanto, Wiryanto (research, training and philanthropy institution Natural Aceh, 2025)
Mathematics learning using the correct Model and approach is important. This is due to the lack of in-depth understanding of mathematical concepts. This qualitative descriptive study uses the Gravemeijer & Cobb Design Research Method. The study was designed to prove the truth of the assumptions that have been written in the learning trajectory or HLT (Hypothetical Learning Trajectory) and its influence on students' conceptual understanding using the RME (Realistic Mathematics Education) approach on the material of weight unit conversion and addition arithmetic operations using Students' worksheet with the topic of the Sidoarjo milkfish auction which is a guideline for student activities. This study was conducted with research subjects of grade IV students of Ma'rif NU Kyai Rodliyah Elementary School. The research subjects were two groups in the class, each with two students. The stages of the research carried out were research preparation, implementation of experimental design, and retrospective analysis. Based on this study, it can be seen that the stages of learning activities with the RME model consist of stages of real-world situations (situations), models that describe problem situations (Model of), models for solving problems (Model for), and stages of formal mathematics with Students' worksheet media that raises the topic of the Sidoarjo milkfish auction can make it easier for students to understand the concept of material regarding the conversion of weight units and their addition arithmetic operations.